Sampling methods for censuses and surveys - Yates, Frank (London : Charles Griffin & Company Limited, 1960)
This book has been written primarily for those who have little or no previous training in mathematical statistics. It has bee made to cover all the modern developments of sampling theory which are of importance in census and survey work.
Includes index.
Includes bibliographical references: p. 401-433.
aia 29/03/2018
Loans
Keywords: Sampling (Statistics); Census